Effect of Change Position and Back Massage on Physiological Parameters for Patients with Back Pain Post-Cardiac Catheterization - Al-Bayati, Kawther Kareem; Al-Kassar, Rajha A. Hamza (Kufa Journal for Nursing Sciences, 2023)
Background: Back pain is frequently reported following cardiac catheterization. This is mainly due to the prolonged bed rest prescribed post-cardiac catheterization, ranging from 3 to 6 h (Masoudi et al.,2017). Aim: To determine the effect of change position and back massage on physiological parameters for patients with back pain post-cardiac catheterization. Methods and Materials: A quasi-experimental design was conducted on patients divided into two study groups. A non-probability (homogenous purposive sample) of (90) patients is included in the present study (30 patients for the study group1,30 patients for study group 2 and 30 patients for the comparison group) where study group 1 received the change position protocol and study group 2 received the change position and back massage. All patients are post-cardiac catheterization and have back pain. Results: Improvement in physiological parameters for patients with back pain in study groups compared with those participants in the comparison group and between the pre-test and three readings of the post-test in the study groups. Conclusion: Implementing the change position and back massage for patients post-cardiac catheterization who have back pain is an effective approach to improve physiological parameters. Recommendations: Future studies should be conducted to determine the effectiveness of the intervention strategy on improving physiological parameters, particularly back pain in combination with other interventions to compare current study's impact with another intervention method for patients with back pain post-cardiac catheterization.